Pendampingan Proyek P5 Pembuatan Poster Konflik Antar Remaja Dalam Meningkatkan Kreatifitas Siswa - Zaini, Muhammad; Hartati, Zainap; Parwanti, Ani (Universitas Pahlawan Tuanku Tambusai, 2024)
The Pancasila Student Profile Strengthening Project (P5) is a government initiative aimed at enhancing students' character through various learning activities. The method used in this community service project is Participatory Action Research (PAR). This article discusses the guidance provided in creating posters about conflicts among teenagers to boost students' creativity at SMPN 8 Palangka Raya, where students are taught to be more creative in making informative and appealing posters on conflict resolution. The main objective is not only to enhance students' creativity in producing informative and attractive posters but also to facilitate meaningful learning processes for the students. The results of the P5 guidance show that the students are very innovative and creative, demonstrating their understanding of the material provided. The P5 project aims to produce informative and attractive posters while also facilitating a meaningful and transformative learning process for the students. It is hoped that this project can contribute to the formation of a younger generation that is not only creative but also possesses a high social awareness and is capable of becoming positive change agents in society.